A novel method of extracting gallbladder specimen in acute cholecystitis: cutting the gallbladder into strips - Kiran, Sadu Shashi; Guduru, Suresh Chandra Hari; Sharma, Deepak; Kore, Pratham; Bandaru, Sai Kishan (International Surgery Journal, 2026)
Background: Acute cholecystitis is a common surgical condition. Laparoscopic cholecystectomy is the standard treatment, but the optimal method for specimen retrieval remains debated. This study evaluates the safety and efficacy of a novel technique involving cutting the gallbladder into strips compared to conventional endobag retrieval. Methods: A retrospective study was conducted at Citizens Specialty Hospital, Hyderabad, from February 2025 to December 2025. A total of 100 patients with acute cholecystitis undergoing laparoscopic cholecystectomy were included. The gallbladder specimen was extracted by cutting it into strips. Data were analyzed using SPSS version 25.0. Patients were followed for two months. Results: No intraoperative or postoperative complications were observed. There were no cases of port-site infection, bile leak, or intra-abdominal abscess. The mean hospital stay was 1.3±0.5 days. Patients reported good postoperative comfort. Conclusions: The technique of cutting the gallbladder into strips is a safe, effective, and cost-efficient alternative to conventional endobag retrieval in laparoscopic cholecystectomy.